JOGOS PLIOMETRIA E CAMPO CONDICIONADO NO TÊNIS - LOS JUEGOS PLIOMÉTRICOS Y LA PREPARACIÓN FÍSICA EN EL TENIS DE CAMPO (Fiep Bulletin - online, 2013)
Plyometrics training is a very efficient method used mainly to generate power, for this reason the intention of the research conducted in Ibague, Tolima Colombia, method was to supplement plyometric moves through forms called "plyometric games", which allowed the training process was conducted and implemented more effectively and efficiently, contributing to a greater willingness and motivation of the athlete during the fitness.The overall objective of the research was to build a plyometric program games as a methodological tool to improve the speed of displacement field players. Since the game Brito, (2000), is a quintessential motor activity, not when the child plays always aware of what you are doing and this is where the teacher or coach plays an important role, it is crucial to note that the teacher when routing the individual through this recreational activity can serve several objectives for this case and sports performance.The research used was cut quantitative quasi - experimental nonequivalent control group (Briones, 2002), the application of plyometric game show was performed at field players 15 and 16 years of different clubs in the city of Ibagué who train and compete nationally representing the Department of Tolima, Colombia.The result is a game-design plyometrics to improve speed of displacement field players between 15 and 16, which consists of three phases built strategically; The implementation of the program of plyometric games tennis field applied evidenced motivation and changes in attitudes towards physical training, proving once again that the methodologies traditionalists can innovate through forms that somehow plays fitness benefit and skill development and motor skills.
Keywords: Games; plyometrics; tennis field.